What is -6 plus 2f plus 3f equals 29?

User Avatar

Wiki User

2011-03-03 15:26:05

Best Answer

-6 plus 2f plus 3f equals 29

-6 + 2f + 3f = 29

-6 + 5f = 29

5f = 35

f = 7

User Avatar

Wiki User

2011-03-03 15:26:05
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
2564 Reviews

Add your answer:

Earn +20 pts
Q: What is -6 plus 2f plus 3f equals 29?
Write your answer...
Still have questions?
magnify glass
Related questions

3f-8 plus 2f equals 47 f is what?


How do you simplify the expression 2f-2 plus 3f?


What is the answer of this problem of 5(2f-1) plus 6-7f-8?

It can be simplified to: 3f-7

What is the answer to this Algebra Math Problem Simplify 2f plus 8 equals 3f-6?

(The equal sign = tells that you are on the other side of the equal sign.)2f+8=3f-6 You want to get the letters on one side.-2f=-2f (I put that equal sign to show that the -2f is on the other side.)8=f-6 3f-2f=f. And now, you want the numbers one just one side.+6=+6 You have to add to get rid of subtract.14=3f Now, you want to solve it by dividing.14/3=3f/3.......... _This line goes with the the answer. It shows that the 6 infinitely repeats. (7)Answers: f = 4.6 or or f = 6.67 or f = 4 2/3 or f = 14/3This is for if line seven (7) was unreadable. It says that the line goes with the answer and that it shows that the 6 infinitely repeats.

3f plus 9 equals 23 what is the value of f?

3f+9 = 23 3f = 23-9 3f = 14 f = 14/3 3f+9=23 -9 -9 3f= 14 /3 /3 f= 4.66666 (6 repeats)

What does -3f-14 equals 1 equals?

If: -3f-14 = 1 Then: f = -5

-3f - 14 equals 1?

-3f - 14 = 1 -3f = 1+14 -3f = 15 f = -5

What does 6 7e plus 5f - 3f equal?


What is 3f minus 2 equals 4f plus 5?

3f - 2 = 4f + 5 You are looking for an unknown number, f. In the end, you want to know that f equals a specific number; the number on one side of the equation and f on the other. So first you want to get it in that format: -2 = 5 + 4f - 3f -2 - 5 = 4f - 3f Now solve: -7 = f You can see that f equals -7. This is what you're looking for.

What are odd and even harmonics?

A harmonic of a wave is a component frequency of the signal that is an integer multiple of the fundamental frequency. If the fundamental frequency is f, the harmonics have frequencies f, 2f, 3f, 4f, etc. Even harmonics are 2f, 4f, 6f, ... Odd harmonics are f, 3f, 5f, ... And remember: Even harmonics 2f, 4f, 6f,... are odd overtones. Odd harmonics f, 3f, 5f,... are even overtones. Scroll down to related links and look at "Calculations of harmonics from fundamental frequency".

What is 3f plus f plus 4f equal?


A father is three times as old as his son After 15 years the father will be twice as old as his sons age at that time Therefore the fathers current age is?

F=3S (a father is 3 times as old as his son) F+15=2(S+15) (after 15 years the father will be twice as old as his sons age at that time) F/3=S F+15=2(F/3+15) F+15=2(F/3)+2(15) F+15=(2F)/3+30 F+15(-15)=(2F)/3+30(-15) F=(2F)/3+15 F(3)=(2F)/3+15)(3) 3F=2F+45 3F(-2F)=2F+45(-2F) F=45

People also asked